Significant augmentation of proton conductivity in low sulfonated polyether sulfone octyl sulfonamide membranes through the incorporation of hectorite clay - Walid Mabrouk; Khaled Charradi; Imen Ben Kacem; Ridha Lafi; Nizar Bellakhal; Riadh Marzouki; Sherif M. A. S. Keshk (Materials for Renewable and Sustainable Energy, 2024)
Abstract An innovative methodology was employed to fabricate ion exchange membranes tailored for fuel cell applications. This approach entailed blending low sulfonated polyether sulfone octyl sulfonamide (LSPSO) with Hectorite (Hect) clay at varying weight percentages (1 wt%, 3 wt%, and 6 wt%). The resultant composite membranes underwent comprehensive characterization via Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, and thermogravimetric analysis, aiming to assess their surface morphology and thermal resilience. Remarkably, the thermal stability of the composite membrane exhibited a substantial enhancement in comparison to the pristine LSPSO membrane. Moreover, the incorporation of 6 wt% Hectorite into the composite membrane yielded a noteworthy amplification in proton conductivity, achieving a fourfold increase (141.66 mS/cm) as opposed to the LSPSO membrane in isolation (35.04 mS/cm). Consequently, the Hect/LSPSO composite membrane exhibits remarkable potential as an electrolyte membrane for fuel cells operating at temperatures surpassing 100 °C.